The Influence of Quality of Work Life (QWL) and Employee Engagement on Organizational Citizenship Behavior (OCB) of Dalmas Members of Ditsamapta Polda DIY with Resistance to Change as A Moderating Variable - Dwi Rismanto, Lukman; Chandra Kirana, Kusuma; Subiyanto, Didik (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - The objective of this research is to investigate how Employee Engagement impacts Organizational Citizenship Behavior (OCB) with Resistance to Change as a moderating factor among Dalmas Ditsamapta Polda DIY personnel. The study utilizes a quantitative method with Structural Equation Modeling (SEM) for analysis. Participants were selected through purposive sampling, focusing on Dalmas Ditsamapta Polda DIY personnel who are at least 18 years old. Data were collected through a Likert scale-based questionnaire and analyzed using WarpPLS version. Design/methodology/approach - This study employs a quantitative research design, using Structural Equation Modeling (SEM) for data analysis. Participants were selected through purposive sampling, focusing on Dalmas Ditsamapta Polda DIY personnel aged 18 and above. Data collection was conducted via a Likert scale-based questionnaire, and analysis was performed using WarpPLS version. Originality -  This research contributes to the existing literature by examining the role of Employee Engagement in influencing Organizational Citizenship Behavior (OCB) within a police institution, with Resistance to Change as a moderating factor. The study enriches theoretical discussions on OCB, particularly in the context of law enforcement. Findings and Discussion - The results showed that: (1) Quality of Work Life (QWL) has a significant effect on OCB, where a comfortable and supportive work environment can increase personnel's voluntary work behavior, including willingness to work overtime. (2) Employee Engagement does not have a significant effect on OCB, which indicates that the company's lack of communication and involvement with personnel leads to low appreciation and work motivation. (3) Resistance to Change is shown to moderate the relationship between QWL, Employee Engagement, and OCB. Personnel facing new regulations often feel anxious and are encouraged to improve skills through collaboration between team members. Conclusion - This research provides a theoretical contribution to the study of OCB, particularly in police institutions. It highlights the importance of increasing personnel engagement and building a supportive work environment to foster more positive work behaviors. Further research is encouraged to explore different variables and analysis methods to gain broader insights into the factors that influence OCB.